Aspek Perpajakan dalam Transfer Pricing dan Problematika Praktik Penghindaran Pajak (Tax Avoidance) - Lingga, Ita Salsalina (Zenit, 2012)
The up rise of globalization in these modern times has resulted in the rapid growth of multinational trade  and cross-border intercompany transactions (related parties transactions). In a global economy where multinational enterprises (MNEs) play a prominent role, many transaction normally take place between members of the group. This phenomena has brought impact to the practice of transfer pricing.  The purpose of transfer pricing are to achieve performance evaluation and optimal determination of taxes. Transfer prices are significant for both taxpayers and tax administration because they determine in large part  the income and expenses, and therefore taxable profits, of associated enterprises in different tax jurisdictions.  In order to regulate the practice of transfer pricing and tax avoidance, Directorate General of Taxes has made regulations that govern the authority to realocate transfer price among divisions that have related parties.  Keywords: transfer pricing, tax avoidance, arm’s length principle